PENDUGAAN PEUBAH POHON DAN PEUBAH TEGAKAN JATI MENGGUNAKAN CITRA UNMANNED AERIAL VEHICEL (UAV) DI KPH RANDUBLATUNG (Jurnal ForestrIndo, 2024)
Forest inventory using remote sensing is an alternative to taking data in the field precisely and quickly. This study aims to identify the ability of UAV imagery to estimate the variables of teak stands of age class XIV with a flight altitude of 90 meters in KPH Randublatung. The method of data collection in the field is to make a plot in the form of a square with a size of 80 m x 80 m by purposive sampling based on slope level criteria. The aerial photography data was processed using PIX4Dmapper and ArcMap 10.5 software to produce the Canopy Height Model (CHM) and crown delineation. Tree variables, such as tree height can be estimated by visual height from CHM with R2 0,777, tree diameter and crown diameter can be estimated by visual crown diameter with R2 respectively 0,460; 0,475. Stand variables, such as stand height, can be estimated by visual average estimated height from CHM with R2 0,826. Stand diameter, crown diameter, stand base area, and number of trees can be estimated by visual average crown diameter with R2 respectively 0,486; 0,464; 0,478; 0,342. Therefore, UAV Imagery can  estimate tree variables and stand variables of XIV age class teak in KPH Randublatung.